(untitled) (Chemical Engineering Research Bulletin, 2021)
Textile and apparel industries are the major role-players in the fast-growing economy of Bangladesh. However, the textile sector consumes a large amount of water for various wet processing operations. Currently 98% of the water used by local textile factories is groundwater, which is causing depletion of ground water levels at a high rate. Considering the gravity of groundwater crisis in future, Bangladesh Government and international brands and retailers are advocating local textile factories to reuse textile effluents and implement ZLD (zero liquid discharge) option in the upcoming years. However, it is a new concept for Bangladesh textile sector, and there is limited understanding regarding technical and economic issues associated to advanced treatment and reusing textile effluent. In this paper, a case study is presented to analyse the application of advanced membrane treatment of conventional ETP (effluent treatment plant) treated water of a denim washing factory. The corresponding technical and economic issues of water recycling and reusing were also analyzed. The selected denim washing factory runs a conventional biological effluent treatment plant (ETP) which satisfies the basic requirements of national and international standards. For advanced treatment, a mobile setup of ultrafiltration (UF) and reverse osmosis (RO) unit was used at factory premises to further treat ETP treated water. The advanced treatment was carried out for three different permeate to reject ratios to observe changes in the permeate and reject water quality. Capital expenditure and operational costs were also assessed to see the economic feasibility of the approach. This study will help local textile factories with real time data to understand the technical and economic issues associated to reusing textile wastewater as process water. Chemical Engineering Research Bulletin 21(2020) 127-132